Dual Band U-Shaped Microstrip Antenna - El-Ashmawy, Nessma Ibrahim; Allam, A.M. M. (Journal of Advanced Research in Applied Mechanics, 2020)
A design of a dual band coaxial fed microstrip U-shaped antenna is presented. It contains a metallic U-shaped patch printed on the substrate and a slot etched in the ground. The antenna has an overall size of 36mm x 34mm, suitable for portable applications. A Rogers RO4350 substrate with a relative permittivity of 3.66, tangential loss of 0.004, and thickness of 1.524mm is used for implementation. The simulated and measured results show that the antenna operates at frequencies 1.22GHz, and 5.7GHz with bandwidths 20MHz, and 90MHz respectively. It fulfils the requirements of GPS and Wireless Sensor Networks applications. The design criteria of this antenna as well as the outcome of the experimental results are presented in this paper. The measured and simulated results are in good agreement.